MANAGEMEN PENDIDIKAN AGAMA ISLAM DALAM KELUARGA KARIR (STUDI KASUS DI DESA TAMANAYU KECAMATAN PRONOJIWO) - Zamzami, Muhammad; Fanani, Zainuddin (PAI RAFAH, 2023)
This study discusses challenges and strategies in the management of Islamic religious education in families with career backgrounds in Tamanayu Village, Pronojiwo District. This study uses qualitative research methods to collect data in the form of words or descriptions. Data were obtained through interviews, field notes, photos, videos, personal documents, and other documents. The main findings of this study indicate that parents' busyness in their careers is the main factor hindering sufficient time to consistently provide religious education. Limited knowledge and understanding of parents about Islamic religious teachings is also an obstacle in teaching religious values to their children. The integration of religious values into a busy family routine is also a challenge. Some of the strategies and practices recommended in the management of Islamic religious education in career families include scheduling special time for religious education, utilizing technology as a tool, and involving children in religious activities in their environment. By implementing this strategy, Islamic religious values can be better integrated into the daily lives of career family children. This research is expected to provide effective solutions and recommendations for improving the management of Islamic religious education in families with career backgrounds. The results of this study are expected to contribute to a better understanding of the importance of religious education in career families and how to overcome the challenges that exist